Studi Kasus Pengaruh Pergeseran Muatan Terhadap Stabilitas Kapal di MV. Kutai Raya Dua - Sriantini, Ari; Ebdasari, Ary Dhevi Dwi (Universitas Hang Tuah, 2023)
Handling and regulating cargo on board is very important to do so that the ship has good stability, as a support in shipping safety. This research is qualitative research using the case study method. This study aims to determine the effect of cargo shifts on ship stability and how to overcome it so that the ship still has good stability and can sail safely and safely. The subject of this study was Chief Officer in MV. Kutai Raya Dua. The data collection technique uses documentation, observation, and interviews. From the calculation of stability after loading activities, it is known that the ship experienced a slope of 2.47° to the right and the GM of the ship by 1.16 meters. To overcome this slope, Chief Officer ordered the crew to move the cargo from the right center line to the left center line with a distance of 2 m, as much as 189,447 tons. With the transfer of cargo from right to left center line, the ship is upright again. So, the occurrence of a shift in cargo on board will cause a tilt on the ship. If the slope is not immediately resolved, it will endanger the cargo, ship, and crew.